Forebrain control of breathing: Anatomy and potential functions - Schottelkotte, Karl M.; Crone, Steven A. (Frontiers in Neurology, 2022)
The forebrain plays important roles in many critical functions, including the control of breathing. We propose that the forebrain is important for ensuring that breathing matches current and anticipated behavioral, emotional, and physiological needs. This review will summarize anatomical and functional evidence implicating forebrain regions in the control of breathing. These regions include the cerebral cortex, extended amygdala, hippocampus, hypothalamus, and thalamus. We will also point out areas where additional research is needed to better understand the specific roles of forebrain regions in the control of breathing.